2011
DOI: 10.15517/rgac.v0i30.7284
|View full text |Cite
|
Sign up to set email alerts
|

Emisión difusa de dióxido de carbono en el Volcán Irazú, Costa Rica

Abstract: The first study of diffuse CO 2 degassing was performed at Irazú volcano in 2001, with the goal to evaluate the origin and spatial distribution of CO 2 efflux as well as the total output of CO 2 to the atmosphere. Most of the study area showed background values of CO 2 efflux, < 20 g m -2 d -1 . The highest value was 316 g m -2 d -1 , which is relatively lower than the observed highest values for other volcanic systems within the same volcano-tectonic framework. The relatively high CO 2 efflux values were loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…In our case, Turrialba volcano has experienced a reawakening process which has lasted ∼20 years (Martini et al, 2010;de Moor et al, 2016a) and Poás' activity is particularly variable (Fischer et al, 2015;de Moor et al, 2016b) and seems to have stages of enhanced volcanic activity and stages of quiescence that alternate every 6-12 years (Rymer et al, 2000(Rymer et al, , 2005(Rymer et al, , 2009. Diffuse degassing monitoring could thus be an interesting tool for long term monitoring (Allard et al, 1991;Chiodini et al, 1996Chiodini et al, , 1998Chiodini et al, , 2001Giammanco et al, 1998;Hernández et al, 1998Hernández et al, , 2001Melián et al, 2001Melián et al, , 2010Salazar et al, 2001;Shimoike et al, 2002;Hernández Perez et al, 2003;Carapezza and Granieri, 2004;Galindo et al, 2004;Lewicki et al, 2005;Notsu et al, 2006;Werner and Cardellini, 2006;Carapezza et al, 2009;Viveiros et al, 2010;Peltier et al, 2012;Werner et al, 2014).…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…In our case, Turrialba volcano has experienced a reawakening process which has lasted ∼20 years (Martini et al, 2010;de Moor et al, 2016a) and Poás' activity is particularly variable (Fischer et al, 2015;de Moor et al, 2016b) and seems to have stages of enhanced volcanic activity and stages of quiescence that alternate every 6-12 years (Rymer et al, 2000(Rymer et al, , 2005(Rymer et al, , 2009. Diffuse degassing monitoring could thus be an interesting tool for long term monitoring (Allard et al, 1991;Chiodini et al, 1996Chiodini et al, , 1998Chiodini et al, , 2001Giammanco et al, 1998;Hernández et al, 1998Hernández et al, , 2001Melián et al, 2001Melián et al, , 2010Salazar et al, 2001;Shimoike et al, 2002;Hernández Perez et al, 2003;Carapezza and Granieri, 2004;Galindo et al, 2004;Lewicki et al, 2005;Notsu et al, 2006;Werner and Cardellini, 2006;Carapezza et al, 2009;Viveiros et al, 2010;Peltier et al, 2012;Werner et al, 2014).…”
Section: Introductionmentioning
confidence: 64%
“…The same procedure was applied to Galindo et al (2004) work for Irazú volcano, who investigated in fact over an area of 3,500,000 m 2 . " * " Means that results were normalized regarding the 2015 investigated area.…”
Section: Irazúmentioning
confidence: 99%
See 1 more Smart Citation
“…Irazú Volcano also presents an important diffuse CO 2 flux: Galindo et al (2004) established a CO 2 base flux at ~20 gm -2 d -1 and maximum values of 316 g m -2 d -1 for sites studied in 2001, while Epiard et al (2017) reported maximum values of 2.71 x 10 4 gm -2 d -1 for the northern flank and 2.17 x 10 3 gm -2 d -1 north of the main crater in 2015. Those diffuse CO 2 flux anomalies are located in areas close to active fault traces, being the structural control very important for the escape of gases and associated rock alteration, but probably with less relevance for the formation of speleothems in the caves of the Irazú Volcano.…”
Section: Fumaroles and Diffuse Gas At Irazú Systemmentioning
confidence: 99%
“…1A). This area is characterized by its intense volcanic influence, with relevant CO 2 emissions (Galindo et al, 2004;Epiard et al, 2017) and evidence of passive fumarole activity and hydrothermalism (Alvarado et al, 2006). Here, we discuss factors related to minerogenesis, the formation of the caves themselves and their linkage with the hydrothermal system.…”
Section: Introductionmentioning
confidence: 99%